An exploration research of the independent college operation efficiency indicators based on DEA. Issue 2 (29th July 2014) - Naiming Xie, Dr Yingjie Yang and Dr Chuanmin Mi, Professor; Hong, Lin; Chen, Xue-Fen; Wang, Yu; Li, Qin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to evaluate the teaching performance of the independent colleges by the method of data envelopment analysis (DEA) comprehensively. Design/methodology/approach – The DEA has become an available way to evaluate the similarity between input and output in several production department and non-production department. The similarity also is comparative efficiency because the way is based on goal linear programming in which there is inner layer of manufacture or fixed input increase output, and output which makes cost minimization of input minimum gets a comparative efficiency of decision making unit. Findings – The results show that an ideal teaching performance never relies on only way because the hysteresis effect of teaching outcome is known for a longer time. Just as the reason, some people argue about the performance evaluation. However, the teaching activity is a great investment. In face of few resources, the benefits of education are not easy to solve these problems. The key point is how to evaluate problems rather than giving up the evaluation. Originality/value – The paper is an exploration research of the teaching performance of independent colleges based on DEA, which not only means some theoretical value, but also means a strong realistic meaning.